3,3′-Diindolylmethane improves pathology and neurological outcome following traumatic brain injury - Carlos A. Dallera; Fabiola Placeres-Uray; Patrizzia Mastromatteo-Alberga; Maria Dominguez-Torres; Alyssa F. Balleste; Aditi S. Gorthy; Tyler S. Rahimzadeh; Isabelle Aliancin; W. Dalton Dietrich; Juan Pablo de Rivero Vaccari; Irwin C. Jacobs; Elizabeth A. Chlipala; et al. (Neurotherapeutics)
3,3′-Diindolylmethane (DIM), a naturally occurring bis-indole found in cruciferous vegetables and produced in small amounts in the normal flora of the human gut, has demonstrated neuroprotective benefits in models of CNS hypoxia and stroke. In the CNS, DIM modulates the activation of the aryl hydrocarbon receptor (AhR) and inhibits its pro-inflammatory effects. Although capable of crossing the blood brain barrier, DIM's bioavailability is limited by its low solubility. Dispersed BR4044 provides a nanoscale high-solubility DIM suspension with the potential for treating traumatic brain injury (TBI). The present study aimed to determine whether BR4044 treatment could reduce pathology and improve behavioral recovery following moderate TBI. Male Sprague Dawley rats received moderate fluid percussion injury or sham surgery followed by vehicle or BR4044 treatment in the acute recovery period. TBI BR4044 animals showed significantly reduced cortical and hippocampal edema and lower levels of serum-derived extracellular vesicles compared to TBI Vehicle animals. BR4044 treatment of TBI animals preserved sensorimotor function and associative fear memory. Cortical contusion size and neuronal loss in the parietal cortex and CA3 region of the hippocampus were also significantly reduced with BR4044 treatment. BR4044 also decreased microbleeding and nuclear AhR at the contusion site. This translational study demonstrates that BR4044 ameliorates pathology and improves neurological outcomes following TBI by reducing brain edema, lowering acute extracellular vesicle release, modulating AhR, preserving cortical and hippocampal neurons, reducing red blood cell (RBC) extravasation into the injured brain, and promoting behavioral recovery.